1, 2, 6-Oxadithiane 2, 2, 6, 6-tetraoxide as an Advanced Electrolyte Additive for Li[Ni0.5Mn0.3Co0.2]O2/Graphite Pouch Cells. Issue 12 (1st January 2019) - Ma, Xiaowei; Young, R. S.; Ellis, L. D.; Ma, Lin; Li, Jing; Dahn, J. R.
Abstract : 1, 2, 6-oxadithiane 2, 2, 6, 6-tetraoxide (ODTO) as a novel electrolyte additive was evaluated in both uncoated and coated single crystal Li[Ni0.5 Mn0.3 Co0.2 ]O2 /graphite pouch cells with 1.2M LiPF6 in ethylene carbonate (EC): ethyl methyl carbonate (EMC) (3:7 by weight) as the electrolyte. ODTO passivates the graphite negative electrode at ∼1.4V (vs. Li/Li + ) and also forms a solid electrolyte interphase layer at the positive electrode side. X-ray photoelectron spectra of cells filled with 1% ODTO demonstrate that ODTO mainly converted to sulfur-containing species at both electrode surfaces after formation. The performances of cells containing up to 5% ODTO and binary additive blends including 2% vinylene carbonate (VC) + 1% ODTO, 2% fluoroethylene carbonate (FEC) + 1% ODTO and 1% LiPO2 F2 + 1% ODTO were evaluated and compared to cells with 2% VC, 2% FEC and 1% LiPO2 F2 . Ultra-high precision coulometry (UHPC) and long-term cycling show that 3% ODTO alone increased coulombic efficiency (CE) and led to high capacity retention for both uncoated and coated cells. Cells with uncoated NMC532 and additive blends containing 1%ODTO along with 1%LiPO2 F2, 2% VC or 2%FEC showed virtually identical cycling performance to cells with coated NMC532 and the same electrolytes, suggesting that coatings are not required if effective additives are used.